PERILAKU MEROKOK ANAK PUTUS SEKOLAH DI WILAYAH PERKOTAAN DAN PERDESAAN - Yunindyawati Yunindyawati (Publikasi Penelitian Terapan dan Kebijakan, 2020)
The aim of this research was to understanding of Smoking Behaviour of Children Drop Out of School in City and Rural Area (Comparation Study in Kayu Agung and Lempuing District Of OKI). Mix method between quantitative and qualitative was used. There were 100 respondent of Children Drop out of School that observed. The result showed that some factors influencing of Smoking Behaviour of Children Drop out of School in City and Rural Area were internal and external factors. Internal factor connected with personality of children. External factors correlated with family environment and peer group. Condition Psychology of children depend on age, reason to smoking, knowledge about smoke, and motivation to stop smoking. Family factors influencing behaviour of smoking were number of people in home that smoking, knowing parent about behaviour smoking of children, punishment and school degree of parent. Environment factors among; information about smoke, how activity of smoking, with who, and friend influence to smoking.